2022
DOI: 10.1007/s11252-022-01291-y
|View full text |Cite
|
Sign up to set email alerts
|

Management is more important than urban landscape parameters in shaping orthopteran assemblages across green infrastructure in a metropole

Abstract: Urbanisation significantly shapes species abundance, diversity, and community structure of invertebrate taxa but the impact on orthoptera remains widely understudied. We investigated the combined effects of spatial, urban landscape and management-related parameters. Additionally, we discussed different sampling strategies. We sampled orthopteran assemblages on green infrastructure associated with the public transport system of Vienna, Austria. Sampled areas include railroad embankments, recreational areas or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Increasing habitat heterogeneity in urban habitats may therefore help to counteract to a certain extent the often‐described homogenization of urban species communities (Piano et al, 2020). Huchler et al (2022) have correctly stated that urban species communities are significantly shaped by management and its consequences for habitat structure. This becomes even more evident when not only diverse and multifaceted plant communities with high and dense cover are considered but also highly disturbed areas with open bare ground (Schwarz & Fartmann, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increasing habitat heterogeneity in urban habitats may therefore help to counteract to a certain extent the often‐described homogenization of urban species communities (Piano et al, 2020). Huchler et al (2022) have correctly stated that urban species communities are significantly shaped by management and its consequences for habitat structure. This becomes even more evident when not only diverse and multifaceted plant communities with high and dense cover are considered but also highly disturbed areas with open bare ground (Schwarz & Fartmann, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies examining the biological and functional diversity of grasshopper species in relation to urban habitat parameters and urban matrix variables. Most studies reported decreasing overall diversity of grasshopper species with increasing urbanization levels (Cherrill, 2015; Melliger et al, 2017; Penone et al, 2013; Piano et al, 2020), but some failed to establish these relationships (Huchler et al, 2022). Vegetation structure and its mowing regime have been shown to be important for urban grasshopper diversity (Eckert et al, 2017; Huchler et al, 2022), but this also applies to rural habitats (Ogan et al, 2022; Schirmel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both dry grasslands and wetlands are habitats at high risk of replacement in urban areas, due to their association with geomorphological and edaphic conditions that are also favourable for agricultural/pastoral reclamation and urban development (Labadessa & Ancillotto, 2023). Both these habitats are mostly disappearing at faster rates than others, such as forests, in cities worldwide (Kingsford et al, 2016), and are highly affected by small‐scale management practices (e.g., mowing) that deeply affect the orthopteran assemblages they host (Huchler et al, 2022). In our specific case, the most recent development in Rome included both urban development/expansion at the expense of formerly agricultural areas and reclamation of abandoned sites (Filibeck et al, 2016), the latter resulting in deeply modified floral assemblages that show lower suitability to orthopterans associated with dry grasslands.…”
Section: Discussionmentioning
confidence: 99%